UPAYA MENINGKATKAN KECERDASAN LOGIKA MATEMATIKA ANAK USIA 5-6 TAHUN MELALUI PERMAINAN KANTONG GEOMETRI - Hazanah, Suherman, Yayah Rukhiyah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
Children's mathematical logic abilities need to be developed from an early age. Interesting media is one of the teaching aids to improve mathematical logic intelligence, namely the geometric bag game which is able to understand the concept of numbers, recognize geometric shapes, state the order of numbers and recognize several colors. The results of observations at TKS Tunas Bangsa Group B found that most of the children were still low because there were still many children who were not able to understand the concept of numbers, recognize geometric shapes, state the order of numbers and recognize several colors. It is suspected that due to the lack of availability and lack of attractive learning tools and the lack of teacher motivation in teaching, the methods used by teachers are also less varied. The aims of this research are (1) to analyze how to improve the mathematical logic intelligence of children aged 5-6 years through the geometric bag game, (2) to analyze the Geometry Pocket Game at TKS Tunas Bangsa which can improve the mathematical logic intelligence of children aged 5-6 years. This research uses Classroom Action Research (PTK) which is collaborative with the class teacher. Data collection in this research was through observing children's activities in learning for 10 Group B TKS Tunas Bangsa children. The research results showed that in the first cycle it reached 51.6% in the category Sufficient or Starting to Develop (MB). In Cycle II there was an increase reaching 79.6% with the category Good or Developing According to Expectations (BSH). Based on research results, the Geometry Pocket Game can improve mathematical logic intelligence in recognizing number symbols.